Difficulty of the term 'sacred' in light of Confucian thought - Morales Marcos, Carmelo (2021)
It is a reality the difficulty that describing something as sacred or religious brings. Another important reason has also been the poor extension capacity of the concept of religion. The Chinese’s religion aversion has much to do with communist ideas. There are enough elements in the Confucian canon texts in order to state that the Confucian tradition has a sacred nature. I have tried to show in this article that, despite all these difficulties, the Confucian tradition meets the requirements to be classified as a sacred tradition